Sundaland’s east–west rain forest population structure : variable manifestations in four polytypic bird species examined using RAD-Seq and plumage analyses - Haw, Chuan Lim; Gawin, Dency F.; Shakya, Subir B.; Harvey, Michael G.; Mustafa, Abdul Rahman; Sheldon, Frederick H. (Blackwell Publishing Ltd, 2017)
Aim: A current model of rain forest population diversification in Sundaland specifieseast–west vicariance into refugia during the early Pleistocene. In some taxa, thisdivision was followed by dispersal and apparent secondary contact on Borneo in thelate Pleistocene. To investigate genetic, morphological, spatial and temporal charac-teristics of the model, we compared genomic population and plumage variationamong four bird species with east–west mtDNA and plumage structure. Location: Borneo and western Sundaland (Sumatra and the Malay Peninsula).Methods: We quantified plumage patterns among populations of two muscicapids(Copsychus saularis and Kittacincla malabarica) and two timaliids (Mixornis gularis andTrichastoma malaccense), and compared them with population genetic patternsdetermined from (1) SNPs produced by RAD-Seq and (2) previously sequencedmtDNA. Results: All four species exhibit east–west variation in morphological and somegenetic characters, but patterns are idiosyncratic. Copsychus saularis’ mtDNA andplumage change gradually across Borneo, but RAD-Seq comparisons indicate nopopulation structure. In K. malabarica, all three characteristics change abruptly andconcurrently on Borneo. In M. gularis, the main east–west break occurs betweenBorneo and western Sundaland, with marginal mtDNA, plumage and RAD-Seq struc-ture on Borneo. T. malaccense exhibits two distinct mtDNA and genomic transitions,an early Pleistocene break between western Sundaland and Borneo, and a Pliocenebreak between the north-east and the rest of Borneo. Despite this deep geneticdivision, its plumage changes clinally across Borneo.Main conclusions: MtDNA, plumage and RAD-Seq patterns may vary depending onsuch factors as pre-Pleistocene distribution, habitat requirements and dispersalpropensity, differential introgression among the three character types, selection onplumage and phylogenetic relationships.